TALENT MANAGEMENT AS HR STRATEGY FOR EMPLOYEE RETENTION: AN ANALYSIS - Behera, R asmita; Mohapatra, A.K. Das (International Journal of Psychosocial Rehabilitation, 2020)
Employees are the key force behind the success of an organization; hence it may not be an exaggeration to say that they are the life blood of the organization. They are the most valuable and critical assets. It is therefore essential not only to attract the best talents but also to retain them. There are of course various factors which influence retention of best talent in the organization. This paper examines the perceptions of employees on factors influencing talent retention in selected public and private sector firms in India. The study has been conducted based on primary data collected through questionnaire from 390 respondents belonging to 30 firms. The data analysed through factor analysis and Principal Component Analysis revealed that working environment, salary, regular training programs, healthy peer relationships, commitment of management, regular communication, appreciating supervisor, implementation of systematic approach etc. are critical to retain employees. Therefore, organisations will have to adopt the strategies, such as fair selection procedure, career advancement schemes, flexible working hours, career advancement schemes, emphasis on personal growth and advancement of the employees depending on the demographic profile of the employees to be able to retain the employees. They may thus use talent management practices as an effective HR strategy for success.